Diurnal variation in transect counts of birds in a cerrado landscape in the state of São Paulo, Brazil - Cavarzere, Vagner; Moraes, Gabriel Parmezani [UNESP] (Soc Brasileira Ornitologia, 2010)
The general statement that birds are recorded more often on morning than on afternoon counts is quite common and widespread among ornithologists. Although many investigators have reported temporal variations in bird detections using Point Counts in temperate regions, few researches regarding the same objectives have been conducted in Neotropical habitats or used transect counts as field method. We used transect counts to test the hypothesis that birds are evenly recorded between times of day in a predominantly open Cerrado landscape in southeastern Brazil. Although not always significantly, the number of species and individuals were consistently greater during the morning counts, which corroborates the fact that birds can be more detectable during this time of day. However, a few families as well as a small percentage of species were more likely to be recorded during either one of the two periods we analyzed. Our results suggest that morning counts should detect higher number of both species and individuals in our study area, but specific taxa show distinct patterns of detection which should be acknowledged prior to sampling.
Keywords: Abundance; Neotropical region; patterns of detection; richness; time of day; visual detection